Development and Preliminary Feasibility Study of a Brief Behavioral Activation Mobile Application (Behavioral Apptivation) to Be Used in Conjunction With Ongoing Therapy. Issue 1 (February 2018) - Dahne, Jennifer; Kustanowitz, Jacob; Lejuez, C.W.
Abstract: Depressive symptoms are the most frequently treated psychiatric condition in the United States. Brief behavioral activation treatment for depression (BATD) is a popular, evidence-based psychotherapy with strong research support for the treatment of depression. In this paper, we describe the development and initial pilot feasibility testing of a BATD mobile application (Behavioral Apptivation) to be used by patients and therapists in conjunction with BATD therapy. We present information regarding the app development process as well as results from a small open-label feasibility trial of the app utilized in conjunction with individual BATD. We include a case series from the open-label trial highlighting how Behavioral Apptivation can be utilized in clinical practice. Highlights: Behavioral Apptivation is a mobile app adjunct to BATD. Behavioral Apptivation consists of a patient mobile app and a therapist Web site. We conducted a small feasibility trial of Behavioral Apptivation used with BATD. Patients on average had a 43% reduction in depression from pre- to posttreatment. Behavioral Apptivation is now available for use by clinicians and patients.